Psychological Factors Affecting the Occurrence of Essential Hypertension in Makassar City General Hospital - Ramba, Yonathan; Suharto, Suharto; Qomaruddin, M. Bagus; Suminar, Dewi Retno; Hendrik, Hendrik (Health Notions, 2018)
The problem with patients with essential hypertension is that they do not know the cause of their illness, so they do not know how to overcome them. In addition, many hypertensive patients who have not received the proper treatment, if they have received treatment, but their blood pressure has not dropped as expected. The purpose of the study is to analyze the psychological factors that influence the occurrence of essential hypertension. This study was an observational study with a cross-sectional design by looking at the influence of psychological factors on the occurrence of essential hypertension. The study population is essential hypertensive patients who seek treatment at Daya Makassar General Hospital. Samples are essential hypertensive patients, aged 20-70 years, minimal education of primary schools and domiciled in Makassar which are obtained by non-probability sampling so that the number of samples is 53 people. Data collection techniques through blood pressure measurement and questionnaire. ANOVA multiple comparison results showed that anger, depression, and mood had a significant effect on the incidence of essential blood pressure, where p Ë Î± = 0.05.